Actuating dalam Perspektif Al Qur’an dan Al Hadits - Khoirunnisaa' Khoirunnisaa' (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
Ummatun or team work that is positioned for yad'u ila al khoiri, invites to good, ya'muruuna bi al ma'ruf, instructs all actions that draw closer to Allah and yanhauna 'ani al munkar preventing what is evil or what is not good, this is an attempt to create cooperation among program implementing staff so that organizational goals can be achieved effectively and efficiently. The actuating function starts from the manager himself to invite or move his members and all components in the organization with three methods of approach, namely bil wisdom, al mau'idhoh al hasanah and al mujJadi al hasaanah adapted to the conditions and level of ability of each